Subclinical Atherosclerosis and Obesity Phenotypes Among Mexican Americans. Issue 3 (March 2015) - Laing, Susan T.; Smulevitz, Beverly; Vatcheva, Kristina P.; Rahbar, Mohammad H.; Reininger, Belinda; McPherson, David D.; McCormick, Joseph B.; Fisher‐Hoch, Susan P.
Abstract : Background: Data on the influence of obesity on atherosclerosis in Hispanics are inconsistent, possibly related to varying cardiometabolic risk among obese individuals. We aimed to determine the association of obesity and cardiometabolic risk with subclinical atherosclerosis in Mexican‐Americans. Methods and Results: Participants (n=503) were drawn from the Cameron County Hispanic Cohort. Metabolic health was defined as <2 of the following: blood pressure ≥130/85; triglyceride ≥150 mg/dL; high‐density lipoprotein cholesterol <40 mg/dL (men) or <50 mg/dL (women); fasting glucose ≥100 mg/dL; homeostasis model assessment of insulin resistance value >5.13; or high‐sensitivity C‐reactive protein >3 mg/L. Carotid intima media thickness (cIMT) was measured. A high proportion of participants (77.8%) were metabolically unhealthy; they were more likely to be male, older, with fewer years of education, and less likely to meet daily recommendations regarding fruit and vegetable servings. One‐third (31.8%) had abnormal carotid ultrasound findings. After adjusting for covariates, mean cIMT varied across the obesity phenotypes ( P =0.0001); there was no difference among the metabolically unhealthy regardless of whether they were obese or not. In multivariable analysis, after adjusting for covariates, cardiometabolic risk ( P =0.0159), but not obesity ( P =0.1446), was significantly associated with subclinical atherosclerosis. Conclusions: In Mexican‐Americans, cardiometabolic risk has a greater effect on early atherosclerosis development than body mass index. Non‐obese but metabolically unhealthy participants had similar development of subclinical atherosclerosis as their obese counterparts. Interventions to maintain metabolic health among obese and non‐obese patients may be a more important goal than weight loss alone.